Analisis Faktor Daya Ungkit Kapasitas Pembangunan Manusia di Kota Malang - Winoto, Suhartono (Jurnal Ilmiah Administrasi Publik, 2018)
People Centered Development are the determinants of successful development that welfare improvement, community trust, social justice, and public participation. This research using dynamic system for analysis of result. The success of development is supported by the leverage factors among others human development capacity, infrastructure development, and public welfare. Then, there are obstacles for improving human development capacity in Malang city is still that a gap, both in the form of gaps in income and opportunities. There were 4 (four) improving the human development capacity among others increased productivity the community, even distribution of opportunities and access to economy sources, the sustainability, and community empowerment.